2020
DOI: 10.1155/2020/8142489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supraorbital Foramen Variations on the Treatment Efficacy of Radiofrequency Therapy for V1 Trigeminal Neuralgia: A Retrospective Study

Abstract: Background. Primary V1 trigeminal neuralgia is a common refractory neuralgia in clinical practice, lacking effective treatments. Radiofrequency therapy has certain treatment efficacy, but its long-term efficacy remained poor and the disease might relapse. Objective. To compare the effects of different types of supraorbital foramen variations on the treatment efficacy of radiofrequency therapy for V1 trigeminal neuralgia. Methods. Data of 54 patients with V1 trigeminal neuralgia who underwent treatment in the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Liu et al (19) have also reported that RFT is an effective and safe therapy for patients with persistent or recurrent trigeminal neuralgia. RFT temperatures ranging from 60 to 95°C are usually used for the treatment of trigeminal neuralgia (20)(21)(22). These studies suggest that RFT with higher temperature is safe and effective in the treatment of trigeminal neuralgia and could reduce the recurrence rate of trigeminal neuralgia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (19) have also reported that RFT is an effective and safe therapy for patients with persistent or recurrent trigeminal neuralgia. RFT temperatures ranging from 60 to 95°C are usually used for the treatment of trigeminal neuralgia (20)(21)(22). These studies suggest that RFT with higher temperature is safe and effective in the treatment of trigeminal neuralgia and could reduce the recurrence rate of trigeminal neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, the 95°C temperature was selected for the RFT of the V1TN with the aim of achieving a complete pain block and improved therapeutic outcomes. Xie et al (22) reported that RFT through the supraorbital foramen was a safer method than through the Gasserian ganglion since it could reduce corneal injury and other complications. Therefore, in this study, we adopted the RFT method through the supraorbital foramen for the treatment of V1TN.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the temperature is, the longer the time, the greater the extent of nerve destruction, and the lower the recurrence rate. However, this treatment can induce a higher probability of adverse complications, such as keratitis or ulcer perforation, excessive numbness of the corresponding innervation area of the trigeminal nerve, and masseter muscle weakness after the operation ( Xie et al, 2020 ). Therefore, during the treatment process, the patient’s treatment benefits and risks should be weighed, and as low a temperature as possible should be selected while still being effective.…”
Section: Minimally Invasive Interventional Therapymentioning
confidence: 99%
“…Therefore, during the treatment process, the patient’s treatment benefits and risks should be weighed, and as low a temperature as possible should be selected while still being effective. In addition, pulsed radiofrequency therapy is available ( Elawamy et al, 2017 ; Telischak et al, 2018 ; Abdel-Rahman et al, 2020 ; Xie et al, 2020 ).…”
Section: Minimally Invasive Interventional Therapymentioning
confidence: 99%
“…However, there are significant contradictions and inconsistencies in the reported clinical results on the efficacy of RF procedures. Most of the clinical studies available in the literature are retrospective studies or case studies limited to reporting high-quality randomized controlled trials [47][48][49][50][51][52][53][54][55]. Furthermore, inappropriate selection criteria and treatment parameters could result in poor treatment outcomes, whereas anatomical variations, which are still not well-established, could limit the accurate interpretation of the obtained results.…”
Section: Heterogeneous Surroundings and Clinical Trialsmentioning
confidence: 99%